2002
DOI: 10.1107/s0108768102005839
|View full text |Cite
|
Sign up to set email alerts
|

Reproducability and transferability of topological properties; experimental charge density of the hexapeptide cyclo-(D,L-Pro)_2–(L-Ala)_4 monohydrate

Abstract: The charge density of a hexapeptide was determined from high-resolution CCD area-detector experiments at 100 K. Two datasets, one from a rotating anode and a second one from synchrotron radiation, were measured and the results are compared. The data are interpreted in terms of the 'rigid pseudoatom' model. The topology of the experimental density is analyzed and compared with the topology of the constituting amino acids, and shows good agreement. All critical points of the electron density at the covalent and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 15 publications
5
38
0
Order By: Relevance
“…Given a well refined high-resolution structure, electrostatic properties may be calculated in different ways: directly by multipolar analysis or using DFT (this work) and͞or QM͞MM methods (34)(35)(36) or by using fragments experimentally (TRF; ref. 27 and this work) or theoretically calculated (37)(38)(39)(40)(41), or by point charge models such as AMBER (29), CHARMM (42), or GRASP (43). This paper has demonstrated that DFT quality potentials can be obtained quickly and almost routinely from high-resolution diffraction data (TRF).…”
Section: Resultsmentioning
confidence: 97%
“…Given a well refined high-resolution structure, electrostatic properties may be calculated in different ways: directly by multipolar analysis or using DFT (this work) and͞or QM͞MM methods (34)(35)(36) or by using fragments experimentally (TRF; ref. 27 and this work) or theoretically calculated (37)(38)(39)(40)(41), or by point charge models such as AMBER (29), CHARMM (42), or GRASP (43). This paper has demonstrated that DFT quality potentials can be obtained quickly and almost routinely from high-resolution diffraction data (TRF).…”
Section: Resultsmentioning
confidence: 97%
“…Atomic properties have also been used empirically to predict several experimental properties including for example, the pK a of weak acids from the atomic energy of the acidic hydrogen [96], a wide array of biological and physicochemical properties of the amino acids, including the genetic code itself, and the effects of mutation on protein stability [60], protein retention times [97], HPLC column capacity factors of high-energy materials [98], NMR spin-spin coupling constants from the electron delocalization indices [99,100], simultaneous consistent prediction of five bulk properties of liquid HF in MD simulation [101], classification of atom types in proteins with future potential applications in force-field design [60,[102][103][104], reconstructing large molecules from transferable fragments or atoms in molecules [60,[105][106][107][108][109][110][111][112][113][114][115][116][117][118][119] (see also Chapters 11 and 12), atomic partitioning of the molecular electrostatic potential [120][121][122], prediction of hydrogenbond donor capacity [123] and basicity [124], and to provide an atomic basis for curvature-induced polarization in carbon nanotubes and nanoshells [125].…”
Section: The Use Of Qtaim Atomic Propertiesmentioning
confidence: 99%
“…Cyclo-(dl-prolyl) 2 -(l-alanyl) 4 Monohydrate: The experimental charge density study of this cyclic hexapeptide by Dittrich et al [40] is based on 100 K synchrotron data and predicts a substantial and significant enhancement of 93(9) %. The Lorentz tensor approach using only point dipoles for the hexapeptide (i.e.…”
mentioning
confidence: 98%